Monochorionic twins with co-win death - detectable yet unpreventable risk to the living twin - Abdullah, Suhaiza; Abd. Aziz, Azian; Ismail, Hamizah; Awang, Mokhtar; R, Anna Liza; A, Baskaran (2010)
27/ Indonesian lady G1P0 @ 38w Twin Pregnancy- MCDA Booking @15w, date confirmed, Both FH seen. No family h/o twin. No h/o taking ovulation induction dugs(married 1year). No underlying medical problem nor family history of congenital anomaly. Antenatally otherwise uneventful. 19w at district clinic: Dx twin pregnancy with 1 fetal demise. She was monitored for fetal growth. Referred to tertiary center at 30w Transabdominal ultrasound – MCDA- 1 st twin-Breech,microcephaly (BPD= 26w), Bilateral CTEV otherwise other structures normal, 2 nd twin- compressed to side wall of uterus. USG show cystic brain changes of survivor.(Figure 1) Amniocentesis - normal chromosomal study Fetal MRI (Figure 2) – Lissencephaly with dilated ventricles and minimal brain tissue seen. This would be compatible with life but very severe mental retardation. Aimed for vaginal delivery in view of poor prognosis of the baby of the living twin. Presented with prelabour rupture of membranes at 38 weeks. Clinically uterus term size, breech, EFW = 2.8-3.0kg. She was induced with PGE2. Delivered via assisted vaginal breech delivery. 1 st twin boy: 2.71kg, AS 8@1, 9@5, COH 28cm; 2 nd twin 300gm- macerated. Placenta examination: Monochorionic Diamniotic. Post natal MRI (Figure 3) confirms the lissencephaly and ventriculomegaly